Comparison of Preoperative Assessment of Patient’s Metabolic Equivalents (METs) Estimated from History versus Measured by Exercise Cardiac Stress Testing - Adam S. Weinstein; Martin I. Sigurdsson; Angela M. Bader (Anesthesiology Research and Practice)
Background. Preoperative anesthetic evaluations of patients before surgery traditionally involves assessment of a patient’s functional capacity to estimate perioperative risk of cardiovascular complications and need for further workup. This is typically done by inquiring about the patient’s physical activity, with the goal of providing an estimate of the metabolic equivalents (METs) that the patient can perform without signs of myocardial ischemia or cardiac failure. We sought to compare estimates of patients’ METs between preoperative assessment by medical history with quantified assessment of METs via the exercise cardiac stress test. Methods. A single-center retrospective chart review from 12/1/2005 to 5/31/2015 was performed on 492 patients who had preoperative evaluations with a cardiac stress test ordered by a perioperative anesthesiologist. Of those, a total of 170 charts were identified as having a preoperative evaluation note and an exercise cardiac stress test. The METs of the patient estimated by history and the METs quantified by the exercise cardiac stress test were compared using a Bland–Altman plot and Cohen’s kappa. Results. Exercise cardiac stress test quantified METs were on average 3.3 METS higher than the METs estimated by the preoperative evaluation history. Only 9% of patients had lower METs quantified by the cardiac stress test than by history. Conclusions. The METs of a patient estimated by preoperative history often underestimates the METs measured by exercise stress testing. This demonstrates that the preoperative assessments of patients’ METs are often conservative which errs on the side of patient safety as it lowers the threshold for deciding to order further cardiac stress testing for screening for ischemia or cardiac failure.